Implementasi Berbasis Nilai – Nilai Kebangsaan UUD 1945 Kajian Undang – Undang Permendag No.21 Tahun 2019 dalam Penerapan Transportasi Perdagangan Kegiatan Ekspor Minyak dan Gas di Indonesia - Edy Soesanto; Dyah Ardhana Mahda Putri; Puspita Dewi Utami (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
The aim of this research is to determine the status of the implementation of the 1945 Constitution (UUD 1945) and Trade Law Number 21 of 2019 in the implementation of commercial transportation for oil and gas export activities in Indonesia based on national values. This research was carried out using analyzes the contents of the 1945 Constitution and Minister of Trade Regulations. A review of relevant literature is included. The national values ​​contained in the 1945 Constitution are an important basis for implementing commercial transportation policies, especially in Indonesia's oil and gas export activities. National values ​​such as unity, sovereignty, justice, democracy and people's welfare are the basis for regulating and supervising these commercial activities. Minister of Trade Regulation Number 21 of 2019 also plays an important role in regulating the transportation of Indonesia's oil and gas export trade. This law contains provisions regarding permits, authorization and safety standards that must be complied with by economic actors in carrying out export activities. The enactment of this law aims to protect national interests, protect the environment, and ensure the safety of oil and gas trade and transportation. This research discusses the analysis of the implementation of the 1945 Constitution and the Minister of Trade Law no. 21 of 2019 which is based on national values ​​in the implementation of commercial transportation for oil and gas export activities in Indonesia. (This analysis includes a review of the policies, procedures and practices implemented in oil and gas export activities. The results of this research are expected to provide a better understanding of the importance of practices based on national values ​​in the implementation of commercial transportation, especially oil and gas export activities, in Indonesia. It is hoped that the implications of this research can become the basis for improving trade policies and practices that are more sustainable, safe, and prioritize national interests and human welfare.